TECHNOLOGY AND COMMUNITY ENGAGEMENT IN SENSITIVE CONTEXTS: REFLECTIONS ON TWO SITE-SPECIFIC SÁMI ART PROJECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Aligned with Sami Center for Contemporary Art (SDG)’s vision to foster cultural and artistic engagement within and beyond the Sámi community, it is important to explore the role of technology applied in the center. This research examines two cases: within an artist talk, and in the form of 3D printing and interactive DIY electronics within the Techno-Lab project, which included a virtual reality (VR) application as part of the installation. As the only place in Karasjok where visitors could experience VR or create prototypes, the center became a meeting point for those interested in art and technology. This study focuses on the authors’ experiences as facilitators in these projects. The research question asks: How can non-Sámi facilitators critically engage with and interpret the dynamic interactions between technology and the local Sámi community in the context of two artistic projects involving trauma-related content? Arts-based research was adopted as the research strategy. The data include field notes, drawings, and photos from the two cases, which were analyzed using a general inductive analysis approach by both authors. The results broadened the authors' understanding of the Sámi community's needs from both physical and emotional perspectives. They also propose a new conceptualization of technology, considering the perspectives of the Indigenous community—particularly marginalized Sámi women—as well as historical contexts. The results highlight the importance of both language and cultural translation within and beyond the Sámi community. Additionally, the authors' reflections on their positionality emphasize the value of fostering an equitable environment where community members, as relative outsiders to different experiences, can learn from one another and share their knowledge. The research provides recommendations on facilitating technology-based community engagement in artistic institutions working with sensitive topics. These findings are valuable for fostering Indigenous autonomy and supporting practitioners at the intersection of technology and facilitation.